New insights into tateid gastropods and their radiation on Fiji based on anatomical and molecular methods (Caenogastropoda: Truncatelloidea). (September 2014) - Zielske, Susan; Haase, Martin
<x xml:space="preserve">Abstract</x> The South Pacific archipelago of Fiji is characterized by a predominantly Indo‐Malesian flora and fauna. We provide a first systematic study on Fiji's tateid gastropods – previously classified as Hydrobiidae – describing 18 new species, combining morphological, anatomical, and molecular data. The molecular phylogeny of tateid gastropods based on 16S rRNA and cytochrome c oxidase subunit I (COI) showed that the species from Fiji were closer related to New Zealand than to Australian or New Caledonian taxa, which is rather exceptional. Performing an ancestral range reconstruction we inferred the colonization history across the two main islands. The radiation had its origin in southern Viti Levu, with a subsequent dispersal over the western and central parts of the island. The chronology of the radiation over eastern Viti Levu and Vanua Levu remained unresolved because of incomplete lineage sorting, a phenomenon typical for young radiations. © 2014 The Linnean Society of London